Pendampingan Literasi Berbahasa Aji di Pondok Pesantren Putri Al-Fathimiyah Banjarwati Paciran Lamongan - Luthfi Hidayah; Mariyam Assa’adatul Mahbubah; Fitri Nur Rohmah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Pesantren is a religious education institution that organizes religious and national education. There are many kinds of pesantren, one of which is a mixed (salafy-modern) pesantren. Like this Al-Fathimiyah Islamic boarding school, in it there is education about religion and technology. Language is one of the means or tools in communicating with others, sometimes using verbal such as speaking, or non-verbal such as facial expressions. The verbal language used by the Indonesian people is Indonesian itself, but it is possible that the Indonesian people can speak foreign languages ​​such as Arabic and English. Likewise an education in pesantren that not only teach Indonesian, but Arabic and English as well. In addition, learning a language is a distinct advantage in order to keep up with the developments of this world's globalization. Learning a foreign language can be done by adding written and spoken vocabulary, because if you only write it you will not necessarily be able to understand how to read it, also if you only speak it you will not necessarily understand how to write it correctly.